2016
DOI: 10.1037/pas0000209
|View full text |Cite
|
Sign up to set email alerts
|

Different types of well-being? A cross-cultural examination of hedonic and eudaimonic well-being.

Abstract: A large international sample was used to test whether hedonia (the experience of positive emotional states and satisfaction of desires) and eudaimonia (the presence of meaning and development of one's potentials) represent 1 overarching well-being construct or 2 related dimensions. A latent correlation of .96 presents negligible evidence for the discriminant validity between Diener's (1984) subjective well-being model of hedonia and Ryff's (1989) psychological well-being model of eudaimonia. When compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
269
3
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(297 citation statements)
references
References 83 publications
13
269
3
12
Order By: Relevance
“…Prior CFA studies have found relatively high correlations ([0.70) between the three components of the MHC-SF in various cultures (Demirci and Akin 2015;Joshanloo et al 2013;Karaś et al 2014). Research with longer versions of the well-being scales has found even larger factor correlations, up to 0.96 (e.g., Disabato et al 2016). These findings intensify concerns over the empirical distinguishability of hedonic and eudaimonic aspects of well-being.…”
Section: Esem Versus Cfamentioning
confidence: 78%
See 1 more Smart Citation
“…Prior CFA studies have found relatively high correlations ([0.70) between the three components of the MHC-SF in various cultures (Demirci and Akin 2015;Joshanloo et al 2013;Karaś et al 2014). Research with longer versions of the well-being scales has found even larger factor correlations, up to 0.96 (e.g., Disabato et al 2016). These findings intensify concerns over the empirical distinguishability of hedonic and eudaimonic aspects of well-being.…”
Section: Esem Versus Cfamentioning
confidence: 78%
“…This concern is justifiable given that the correlations between the psychological (eudaimonic) and the emotional (hedonic) well-being factors have repeatedly been found to be very high in CFA studies. For example, Disabato et al (2016), using CFA, found a correlation of 0.96 between hedonic and psychological wellbeing. However, recent studies using ESEM have consistently indicated that the correlations between the three components of well-being are in fact much smaller than those found in CFA studies if cross-loadings are not fixed to zero.…”
Section: Factor Structure Of the Mhc-sfmentioning
confidence: 96%
“…Nevertheless, differences among the constructs that have been used to define eudaimonic well-being have led some researchers to criticize the distinction between hedonic and eudaimonic well-being (e.g. Disabato, Goodman, Kashdan, Short, & Jarden, 2016;Kashdan, Biswas-Diener, & King, 2008).…”
Section: Hedonic and Eudaimonic Conceptualizations Of Well-beingmentioning
confidence: 98%
“…However, in the light of new analysis, eudaimonic well-being and hedonic well-being are correlated but also relatively independent constructs (Bojanowska and Zalewska 2016;Disabato et al 2016;Joshanloo 2016). According to the theory (Tedeschi and Calhoun 1996), PTG should incorporate these two aspects of well-being: trauma-triggered changes have a potential to make life more meaningful but also more satisfactory.…”
mentioning
confidence: 99%